Stakeholders' perceptions of parents' involvement in the governance of a Namibian rural school - Niitembu, Martha M (Rhodes University, Faculty of Education, Department of Education, 2007)
The issue of decentralisation has been one of the top priorities of the Namibian education system since independence in 1990. One of the decentralisation aims was to enhance parental involvement in education by establishing School Boards. However, School Boards and the role of parents in school management have been considered ineffective for several years which led to the promulgation of Education Act 16 of 2001 in which the roles of School Boards are strengthened and clarified. This study sought to investigate School Board members' perceptions, understanding and experiences of parents' involvement in school governance more specifically after the implementation of the Education Act of 2001 in 2003. This study is an interpretive case study of one combined rural school in the Ohangwena educational region of Namibia. This research employed three data collection techniques, namely semi-structured interviews, observation and document analysis. The main findings of this study reveal that there is a lack of joint understanding and shared vision between educators and parents in the School Board. This problem underpins other more symptomatic problems, such as lack of accountability in the matter of school finances, differences in understanding the roles of School Board members and lack of parents' motivation from the school management. The study further reveals the ineffectiveness and insufficiency of the training provided in the past. It highlights some of the challenges that hinder the effective involvement of parents in rural school governance, such as poor educational background among parents, poor knowledge of the English language and poor understanding of educational issues. However the findings also acknowledge parents' participation and their full involvement in decision-making. The findings show that the new School Board elected in terms of the Education Act of 2001 has been more effective than previous School Boards and has reached a number of achievements such as being instrumental in solving disciplinary problems, purchasing school assets and renovating classrooms. Recommendations for practice and for further research are made.
Keywords: School management and organization -- Namibia; Education -- Parent participation -- Namibia; Education and state -- Namibia; Rural schools -- Namibia